2013
DOI: 10.1111/ejn.12408
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the medium‐duration afterhyperpolarization in rat serotonergic neurons

Abstract: Most serotonergic neurons display a prominent medium-duration afterhyperpolarization (mAHP), which is mediated by small-conductance Ca(2+) -activated K(+) (SK) channels. Recent ex vivo and in vivo experiments have suggested that SK channel blockade increases the firing rate and/or bursting in these neurons. The purpose of this study was therefore to characterize the source of Ca(2+) which activates the mAHP channels in serotonergic neurons. In voltage-clamp experiments, an outward current was recorded at -60 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…A key characteristic of 5-HT neurons is their long-duration action potential followed by a medium duration AHP (Beck et al, 2003; Kirby et al, 2003; Rouchet et al, 2008; Alix et al, 2014). Since AHP modulation is closely linked to the alterations in the firing activity of 5-HT neurons (Rouchet et al, 2008; Crespi, 2009), we sought to determine whether the observed reduction in their activity is due to a more pronounced AHP.…”
Section: Resultsmentioning
confidence: 99%
“…A key characteristic of 5-HT neurons is their long-duration action potential followed by a medium duration AHP (Beck et al, 2003; Kirby et al, 2003; Rouchet et al, 2008; Alix et al, 2014). Since AHP modulation is closely linked to the alterations in the firing activity of 5-HT neurons (Rouchet et al, 2008; Crespi, 2009), we sought to determine whether the observed reduction in their activity is due to a more pronounced AHP.…”
Section: Resultsmentioning
confidence: 99%
“…After breakthrough, a brief series of voltage protocols were delivered to ascertain the presence of A-type K + currents and/or T-type Ca 2+ currents for LDT and PPT cholinergic neurons ( 30 – 32 ) and a strong medium AHP current for DR serotonergic neurons [see Ref. ( 33 )]. Voltage clamp mode was used to record orexin currents in order to assess their spectral characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…One important class of K + channels are the calcium-activated potassium channels (CAKC). CAKCs regulate membrane potential (Gui et al, 2012;Alix et al, 2014;Rohmann et al, 2015;Yang, 2016), cell volume regulation and renal K + excretion (Latorre et al, 2017;Sforna et al, 2018) among other cellular functions.…”
Section: Introductionmentioning
confidence: 99%